2010
DOI: 10.1007/s10530-010-9747-2
|View full text |Cite
|
Sign up to set email alerts
|

Does allelopathy explain the invasiveness of Campuloclinium macrocephalum (pompom weed) in the South African grassland biome?

Abstract: Campuloclinium macrocephalum is an Asteraceous alien weed that invades roadside vegetation and grassland in South Africa. The role of allelopathy and competition in its invasiveness was investigated using Eragrostis curvula (weeping lovegrass, an indigenous grass), E. tef and Lactuca sativa (lettuce) as test species. Trials were conducted in Petri-dishes, pots and in the field. Root and shoot extracts of adult C. macrocephalum plants did not inhibit seed germination in any test species. The greatest effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…native trees or herbs), different types of biological assays have habitually been used. Apparently, the most successful are based on the use of aqueous extracts from the donor plants (Wardle et al 1996, Lin et al 2004, Mutlu & Atici 2009, Zhu et al 2009, Goodall et al 2010, Chon & Nelson 2013 to simulate field conditions (Scognamiglio et al 2013), or even by placing the host seeds in direct contact with the plant structures of the donor species in an aqueous environment (Aguilera et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…native trees or herbs), different types of biological assays have habitually been used. Apparently, the most successful are based on the use of aqueous extracts from the donor plants (Wardle et al 1996, Lin et al 2004, Mutlu & Atici 2009, Zhu et al 2009, Goodall et al 2010, Chon & Nelson 2013 to simulate field conditions (Scognamiglio et al 2013), or even by placing the host seeds in direct contact with the plant structures of the donor species in an aqueous environment (Aguilera et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The impact that pompom weed has on species composition is subtle rather than one that completely transforms the communities it invades. For example, E. curvula and pompom weed were the most dominant species across sites (Appendix), yet in a separate study both species were found to be excellent competitors that coexisted rather than being competitively exclusive under controlled conditions and in the field (Goodall et al 2010). Three theories could contribute to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Henderson 2001), the infestation in Gauteng Province is sufficiently disjunct for the aim of discriminating between factors that facilitate invasion from those that influence vegetation dynamics, and secondly, to determine the impact that pompom weed density has on plant community composition in an isolated megainfestation. The Gauteng infestation, being the original point of introduction in the 1960s (Goodall et al 2010), is considerably larger and more concentrated than in other provinces. By the 1970s it was already widespread around the city of Pretoria with populations ranging from 30,000 to [100,000 plants per site (pers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological traits related to the interception of radiation by leaves which determine competitiveness for light, including leaf size, number and leaf area index, stem elongation, upward leaf movement [21][22][23][24] and leaf layer density [25], have not been studied in canola. These traits are associated with shade avoidance, enabling plants to photosynthesise and grow to improve their competitiveness [21,22].…”
Section: Biological Approaches For Controlling Weedsmentioning
confidence: 99%